Physical and mathematical ponderability of temperature measurement’s frequencyin environmental engineering - Wiesław Kowalski (Acta Scientiarum Polonorum. Formatio Circumiectus)
The paper discusses circumstances that lead to improper measurements of temperature: without appropriate consideration to the context of physical phenomena occurring in nature or without appropriate awareness of mathematical principles; all of which results in data misinterpretation. Based on the conducted discussion, it can be stated that measurements and analyses of thermal phenomena, which are time-varying processes, should be performed using the same principles and tools as in the identification of dynamic processes, such as the Nyquist theorem.